Patterns of bi-national couples across five EU countries - Gaspar,Sofia (2012)
In the past few years, European bi-national couples had been on rise motivated by EU´s mobility policies among its citizens. The aim of this paper is to expand upon a previous analysis of bi-national couples in Spain and Italy (Gaspar, 2011) to another three EU countries - France, Great Britain and Germany. The results revealed the presence of a threefold typology of bi-national couples, partially endorsing some of the patterns found beforehand. In the light of this evidence, the remainder of the article moves towards an understanding of how this typology has to be contextualized within broader specialized migration flows to these countries.